Gambaran Perilaku Agresif Pada Remaja Di Sma Muhammadiyah 10 Genteng Surabaya - Mundakir, Mundakir; Fausi, Muhammad; Wulandari, Yuanita (Jurnal Keperawatan Muhammadiyah, 2024)
Adolescence is a time of change. Changes in adolescence occur very quickly both physically and psychologically, because in this phase adolescents are looking for a lifestyle that is most suitable for them, this is often done by trial and error, even through many mistakes. Aggressive behavior is an overflow of individual emotions that is shown in the destruction of humans or objects with an element of intent that is expressed in words and behavior directly. This study aims to identify physical aggressive behavior, verbal aggressive behavior, anger behavior, and hostile behavior carried out by adolescents at SMA 10 Muhammadiyah Genteng Surabaya. The research design used is descriptive with a qualitative approach. The population of students at SMA Muhammadiyah 10 Genteng Surabaya is 315, with a sample of 176. The data collection technique uses simple random sampling technique. The research variables are Physical Aggressive, Verbal Aggressive, Angry Aggressive and Hostile Attitudes. Data collection using a questionnaire. The results showed that aggressive behavior at Muhammadiyah 10 Genteng Surabaya High School was low Physical Aggressive Behavior (69.3%), Low Verbal Aggressive (93.2%), Low Angry Aggressive (51.1%) and Low Hostility (75.6%). Aggressive behavior in adolescents at Muhammadiyah 10 Genteng Surabaya High School is classified as having a low score. Efforts that can be made to overcome the low aggressive behavior in adolescents at SMA Muhammadiyah 10 Genteng Surabaya is to increase the number of counseling teachers, so that teachers can work optimally in solving student problems and it is hoped that all teachers will also participate in solving student problems so that they can guide and educate students to reduce negative behaviors such as aggressive behavior.